Examining Indonesian Government Policies in Tackling Deforestation: Balancing Economy and Environment - Mahendra, Januar Rahadian; Aldyan, Rizal Akbar; Emovwodo, Silas Oghenemaro (Journal of Law, Environmental and Justice, 2024)
The Indonesian government has implemented specific measures that have negatively impacted the environmental sector to enhance economic growth. In response to worldwide pressure and growing internal awareness, the Indonesian government implemented "pro-environment" policies by endorsing many international and regional accords and revising legislation. This article examines the Indonesian government's policy orientation in addressing deforestation, specifically whether the strategy prioritises economic or environmental considerations. Through the utilisation of normative juridical research methodologies, a statutory approach and a case approach, it was determined that the policies issued by the Indonesian government conflict with one another. These policies encompass several issues. Firstly, granting Forest Concession Rights, which should ideally prioritise forest sustainability, unfortunately, leads to extensive forest destruction. Secondly, the haphazard granting of concession permits is another concern. Lastly, the MP3EI and MIFEE programmes conflict with Law Number 32 of 2009, resulting in a significant loss of 76% of peat land in Papua. Furthermore, the lack of robust law enforcement regarding deforestation also exacerbates the accelerated pace of deforestation. Thus, it is evident that the Indonesian government is giving more importance to the economic sector than the environmental sector.